Low cost and compact nonlinear (SHG/TPE) laser scanning endoscope for bio-medical application - Lim, Ken Choong (2015)
Two-photon fluorescence (TPE) and second harmonic generation (SHG) can been used to extract biological information from tissues at the molecular level, which is blind to traditional microscopes. Through these two image contrast mechanisms, a nonlinear laser scanning endoscope (NLSE) is able to image tissue cells and the extra cellular matrix (ECM) through a special fiber and miniaturized scanner without the requirement of poisonous chemical staining. Therefore, NLSE reserves high potential for in-vivo pathological study and disease diagnosis. However, the high cost and bulky size of a NLSE system has become one of the major issues preventing this technology from practical clinical operation. In this paper, we report a fiber laser based multi-modality NLSE system with compact size and low cost, ideal for in-vivo applications in clinical environments. The demonstration of the developed NLSE nonlinear imaging capability on different bio-structures in liver, retina and skin are also presented.